Beyond Horizons: The Lived Experiences of Social Studies Teachers in Teaching Out-of-Field Subjects - Candelaria Landicho, Jedielyn (International Journal on Integrated Education, 2025)
Out-of-field teaching has increasingly challenged the Philippine education system, particularly in public secondary schools. This study explores the lived experiences of Social Studies teachers in Cabuyao City who were assigned to teach subjects beyond their specialization, such as MAPEH, TLE, Filipino, and Values Education. Guided by Vygotsky’s Social Constructivist Theory and Shulman’s Pedagogical Content Knowledge framework, a qualitative phenomenological research design was employed. Data were collected through semi-structured interviews with ten purposively selected teachers and analyzed using Colaizzi’s seven-step method. The analysis revealed two major themes: (1) Challenges Faced When Teaching Outside Expertise, and (2) Adaptive Strategies for Overcoming Out-of-Field Teaching Challenges. Key challenges included subject mastery gaps, difficulty in lesson delivery, lack of curriculum resources, increased preparation time, and anxiety. Despite these, participants demonstrated resilience by seeking peer support, attending professional development seminars, diversifying their teaching strategies, and embracing lifelong learning. Motivation, flexibility, and administrative support were vital to their ability to navigate these difficulties. Findings emphasized the importance of continuous professional development, mentorship, and institutional support systems to aid out-of-field teachers. The study concludes that while teaching outside one’s specialization imposes significant instructional and emotional challenges, it also offers opportunities for professional growth, adaptability, and innovation in teaching practices. These insights are critical for shaping educational policies and support programs that can better equip teachers to handle the demands of out-of-field teaching and enhance overall educational quality.